Revitalization of Tourism Products as a Tourism Marketing Strategy Moderated by Destination Image on Visiting Decisions - Alifian Rizzalul Ahmad; Diana Kusuma Nurjannah (Medikun Publisher, 2024)
Indonesia's tourism industry has rebounded with increased foreign exchange earnings following the pandemic-induced downturn. Tourism plays a crucial role in both domestic and international market development. A critical effort in the tourism marketing development strategy is revitalizing tourism products. Wisata Rembangan in Jember, East Java, underwent tourism product revitalization due to deteriorating facilities and visitor dissatisfaction during 2015-2020. This effort aimed to enhance destination appeal and visitor numbers. This study explores how Wisata Rembangan's product revitalization influences visitor decisions, with destination image as a moderating factor. Positive impacts are anticipated on repeat visits due to improved tourism products. While destination image influences visitor decisions, it does not significantly moderate the effect of product revitalization. Practical recommendations will aid Rembangan Tourism in enhancing destination quality and competitiveness through effective strategies. This research employs an explanatory approach with questionnaire-based data collection from Rembangan visitors, analyzed using PLS-SEM. Findings indicate a direct positive relationship between tourism product revitalization and visitor decisions, with destination image contributing positively but without significant moderation effect.